1 - Women Engagement with Power and Authority in Re-writing East Africa: https://doi.org/10.4314/ad.v35i4.70214 - Odiemo-Munara, Lennox (Africa Development, 2021)
From the relative absence of serious women writing in the early mainstream East African literature in English, starting the last quarter of the twentieth century, women writing has flourished to gain deserved space in the East African literary canon. In the writing of Kenya’s Marjorie Oludhe Macgoye, Uganda’s Mary Karooro Okurut, and Tanzania’s Elieshi Lema, literature in English by women has exponentially broadened, thematically and aesthetically, to adequately carry and represent the East African woman person’s so cio- historical and economic experiences as well as her private/public narratives. This literature perceives the woman in both the specific and broader historical and cultural realms of the East African society. It shows how she, with intellectual and emotional maturity, interrogates practices and institutions that are, in most cases, patriarchally constructed, in order to evolve a gender inclusivist and all-encompassing human space. Three works by these authors – Macgoye’s The Present Moment (1987), Okurut’s The Invisible Weevil (1998), and Lema’s Parched Earth: A Love Story (2001) – clearly stand out in their contribution to the mapping of unique paradigms in (re)defining the East African woman’s experience in her relation and engagement with the public sphere. This article demonstrates how these writers, through the women figures in the texts, subvert, actively resist, and engage with power/authority and, in the process, manage to re-evaluate the dominant zeitgeist, oppositionally establishing the East African woman as an active and speaking subject in the ongoing re-imagining and re-writing of the East African post-colonies.